Patogenicidade de Fusarium spp. a grão-de-bico e controle biológico com Trichoderma sp. - Daiana Maria Queiroz Azevedo (2015)
The chickpea (Cicer arietinum L.) is a leguminous of great importance worldwide due to its high content of protein, iron, vitamins and fiber. The production of this leguminous is limited by the occurrence of diseases caused by Fusarium, which has hindered the deployment of the culture in Montes Claros and other Brazilians regions. Fungi of the Trichoderma gender are widely known to act as antagonists to various pathogens. The objective of this study was to obtain, identify and evaluate the pathogenicity of Fusarium sp. associated with chickpea and evaluate the potential antagonist Trichoderma isolates in vitro and in vivo control to the Fusarium spp. Fusarium isolates obtained from chickpea plants with apparent fusarium symptoms caused by Fusarium were characterized by morphological and phylogenetic parameters. Among the micromorphological characteristics were evaluated the size, shape and septation of microconidia and macroconidia; conidia production in false heads; presence and coloring sporodochia and type and size of phialides and chlamydospores. The phylogenetic analysis was performed based on comparison of partial sequences of the gene encoding elongation factor EF-1 species with sequences of the Fusarium oxysporum (FOSC) species complex and Fusarium solani species complex (FSSC) available in GenBank-NCBI. Two pathogenicity tests were conducted in a greenhouse. Trichoderma isolates were obtained from the rhizosphere of chickpea plants and were evaluated in vitro as to antagonism to pathogenic isolates of F. solani and F. oxysporum through competition in paired cultures and the production of volatile organic compounds and non-volatile with fungicidal and/or fungistatic activity. In greenhouse four selected Trichoderma isolates were evaluated separately and combined as compared to the commercial product Quality®. Of the 14 isolates of Fusarium obtained and characterized, 11 showed typical morphological markers of F. oxysporum and three of F. solani. According to the phylogenetic analysis, three isolates clustered along the line 3 + 4 of FSSC, while the other 11 isolates clustered in FOSC complex, in a distinct clade of F. oxysporum f. sp. ciceris. All isolates were pathogenic, causing symptoms of yellowing, wilting and root rot. The isolated FCA 12 and FCA 27 were the most aggressive among the isolates of F. oxysporum and F. solani evaluated, respectively. The Trichoderma sp. isolates were efficient competitors and produced volatile metabolites capable of inhibiting the mycelial growth of the two species of Fusarium evaluated. Already the non-volatile metabolites produced by Trichoderma isolates showed low inhibitory activity to F. solani and F. oxysporum and varied as its action. In the evaluation in greenhouse was not observed the effect of treatment with Trichoderma isolated over control of F. oxysporum and F. solani. In this work we demonstrate for the first time phylogenetic position of Fusarium isolates associated with chickpea in cultivated area in Brazil.